2021
DOI: 10.1051/aacus/2021005
|View full text |Cite
|
Sign up to set email alerts
|

Application of the noise annoyance equivalents model for aircraft, rail and road traffic noise to self-reported sleep disturbance

Abstract: Sleep disturbances caused by noise exposure are the most relevant outcome measured in disability adjusted life years (DALYs). In analogy to the combined effects of noise from multiple sources on annoyance, these are also of interest for sleep disorders. The study “Overall Noise Assessment” Innsbruck examined data from 1031 personal interviews. Aircraft, rail and road noise were correlated. To choose participants combined exposures were clustered into small, medium and severely affected living situations. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
6
4
0
Order By: Relevance
“…For road and rail traffic, similar risk estimates were observed (road: OR = 2.86, 95% CI 1.92–4.28; rail: OR = 2.67, 95% CI 2.03–3.50 per 10 dB L night increase). Our results are in line with findings from other European cities, which also observed a stronger association for aircraft noise on the HSD risk compared with road and rail traffic [ 16 , 17 , 48 ]. This indicates that aircraft noise is particularly sleep disturbing.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For road and rail traffic, similar risk estimates were observed (road: OR = 2.86, 95% CI 1.92–4.28; rail: OR = 2.67, 95% CI 2.03–3.50 per 10 dB L night increase). Our results are in line with findings from other European cities, which also observed a stronger association for aircraft noise on the HSD risk compared with road and rail traffic [ 16 , 17 , 48 ]. This indicates that aircraft noise is particularly sleep disturbing.…”
Section: Discussionsupporting
confidence: 93%
“…About 2.7% of participants were classified as being HSD from road traffic noise, 1.2% from rail traffic noise and 2.0% from aircraft noise. Similar prevalence has been reported by Lechner and colleagues for the city of Innsbruck [ 17 ], where the %HSD was 5.5% for road traffic, 1.5% for rail traffic noise and 3.9% for aircraft noise. In the Swiss SIRENE study, a higher HSD prevalence was observed for all traffic sources: the proportion of HSD was 9.3% for road traffic noise, 10.0% for rail traffic noise and 12% for aircraft noise.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Above 58.2 dB, the %HSD_CS increases enormously, reaching 28.57% of people highly annoyed for L night = 64-65 dB, compared to an approximate percentage of 11.20 according to the WHO's study. However, it is within the confidence intervals of the study by Lechner et al [45] carried out in Innsbruck, in the Inntal valley, although with approximately 10% fewer people annoyed at 65 dB. In the study by Lechner et al, however, the degree of annoyance is greater than in the curves of the WHO and Miedema and Vos [46] along the entire curve, and therefore, theirs shows a different trend than our study.…”
Section: Analysis Of the Survey Datasupporting
confidence: 50%
“…Noise affects not only wildlife living near roads [1][2][3][4][5], but according to the WHO, noise is a very serious harmful factor affecting human health [6,7]. Noise pollution causes various health problems, such as cardiovascular disease [8][9][10][11], stroke [12,13], hypertension [14][15][16], mental health problems, stress [11,17,18] and sleep deprivation [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%